Project‐Based Approach as Methodology to Improve Academic Performance of Medical School Students Within the Research Line Teaching Course: A Quasi‐Experimental Study - Ekaterina Kldiashvili; Ivane Abiatari; Maia Zarnadze (Health Science Reports)
ABSTRACT Background and Aims Traditional teaching methods in medical education often fail to engage students or foster critical research skills required for evidence‐based medicine. Project‐based learning (PBL) is widely recognized for promoting active learning and improving academic performance, although its application in research‐focused medical courses remains underexplored, especially in low‐resource settings. This study aimed to evaluate the effectiveness of PBL in enhancing academic performance and originality compared to traditional literature review‐based assessments. Methods A quasi‐experimental study was conducted between March 11, 2024 and May 31, 2024, with 179 twelfth‐semester medical students divided into two groups: the experimental group (PBL approach, n = 108) and the control group (literature review‐based approach, n = 71). Students in the PBL group completed the full research cycle, including topic selection, data collection, analysis, research paper formulation, while the control group focused on synthesizing existing literature. Academic performance (course grades) and originality (Turnitin similarity percentage) were measured. Data were analyzed using descriptive statistics and independent samples t‐tests, with a significance threshold of p < 0.01. Results The PBL group demonstrated significantly higher academic performance (mean: 82.5, median: 85) compared to the control group (mean: 66.5, median: 63.75; t(177) = −20.53, p < 0.01). Similarly, originality improved significantly in the PBL group, with lower similarity scores (mean: 4.17%, median: 4.5%) than the control group (mean: 12.62%, median: 13%, t(177) = 13.74, p < 0.01). Variability in academic performance was slightly higher in the PBL group (standard deviation: 5.80 vs. 4.81), reflecting the individualized nature of PBL. Conclusion This study confirms that PBL significantly enhances academic performance and fosters originality among medical students, particularly in research‐focused courses. The findings underscore the potential of PBL as a transformative approach to medical education, addressing gaps in traditional methods while aligning with global trends in evidence‐based practice and academic integrity. PBL is recommended as an adaptable and effective strategy, especially in resource‐limited educational settings.